Testing of January Effect on the Indonesian Capital Market: Sectoral Analysis of GARCH Models - I Gusti Bagus Wiksuana; Ni Ketut Purnawati; I Made Surya Negara Sudirman. (Faculty of Economics and Business Udayana University, 2021)
January Effect is the stock returns in January are higher than other months. This study uses the Generalized Autoregresive Conditional Heteroscedasticity (GARCH) method to test and analyze the January Effect in the Indonesian capital market from 2000 dd. 2018. The novelty of this study is a research methodology that classifies samples by sector and period on the January Effect test. The results of this study indicate that the January Effect occurs in several sectors and period. The January Effect occurs in the mining sector, consumer goods sector, property sector, and trade sector. Thus, the results of this study confirm the tax loss selling hypothesis and window dressing hypothesis in several sectors and observation periods. This shows that the January Effect is related to the characteristics of the sector and the period of observation.